2023
DOI: 10.3390/su152316269
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection in a Single-Bus DC Microgrid Connected to EV/PV Systems and Hybrid Energy Storage Using the DMD-IF Method

Alireza Sistani,
Seyed Amir Hosseini,
Vahideh Sadat Sadeghi
et al.

Abstract: Variations in fault currents, short times to clear the fault, and a lack of a natural current zero-crossing point are the most important challenges that DC microgrid protection faces. This challenge becomes more complicated with the presence of electric vehicles and energy storage systems due to their uncertainties. For this reason, in this paper, a new method for fault detection in DC microgrids with the presence of electric vehicles and energy storage systems is proposed. The new proposed method uses the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This examination encompassed pole-to-ground (PG)and pole-to-pole (PP) faults on the main line and the faults occurring within the microgrid's distributed energy sources. The case studies examine various fault impedances present in different sections of the DC microgrid, which are commonly investigated scenarios in recent studies [51].…”
Section: Fault Detection Resultsmentioning
confidence: 99%
“…This examination encompassed pole-to-ground (PG)and pole-to-pole (PP) faults on the main line and the faults occurring within the microgrid's distributed energy sources. The case studies examine various fault impedances present in different sections of the DC microgrid, which are commonly investigated scenarios in recent studies [51].…”
Section: Fault Detection Resultsmentioning
confidence: 99%
“…Other authors in [12] presented a new TW-based protection for hybrid DC transmission networks by analyzing TW propagation in the system. Reference [13] introduced a fault detection method for DC microgrids with electric vehicles and energy storage, combining dynamic mode decomposition and instantaneous frequency calculation using voltage and current signals to minimize transient effects. Similarly, authors in [14] suggested a fault detection technique for DC microgrids, merging dynamic mode decomposition and instantaneous frequency calculation from voltage and current signals to reduce transient impacts.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The CR is generated through eq (13) by subtracting measured discrete current from estimated/filtered EKF. The detailed step by step calculation of EKF based CR is mentioned in eq (7) to (13). These steps represent the iterative process within the EKF, where the residual is pivotal in refining the state estimate and improving the accuracy of the filtering process.…”
Section: Fault Detection Index Generation Unitmentioning
confidence: 99%